2001
DOI: 10.3354/dao045009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of infectious salmon anaemia virus (ISAV) from Coho salmon in Chile

Abstract: The isolation of infectious salmon anaemia virus (ISAV) from asymptomatic wild fish species including wild salmon, sea trout and eel established that wild fish can be a reservoir of ISAV for farmed Atlantic salmon. This report characterizes the biological properties of ISAV isolated from a disease outbreak in farmed Coho salmon in Chile and compares it with ISAV isolated from farmed Atlantic salmon in Canada and Europe. The virus that was isolated from Coho salmon tissues was initially detected with ISAV-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 19 publications
3
120
1
4
Order By: Relevance
“…Although epizootics have occurred in Norway since 1984, the disease has only recently been diagnosed in Canada (Mullins et al 1998, Bouchard et al 1999, Lovely et al 1999, Scotland (Rodger et al 1998, Stagg et al 1999, Turnbull 1999, Chile (Kibenge et al 2001), Faroes (Anonymous 2000) and the USA (Bouchard et al 2001). Typical pathological changes are severe anaemia, leucopenia, ascites and haemorrhagic liver necrosis (Thorud & Djupvik 1988, Evensen et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Although epizootics have occurred in Norway since 1984, the disease has only recently been diagnosed in Canada (Mullins et al 1998, Bouchard et al 1999, Lovely et al 1999, Scotland (Rodger et al 1998, Stagg et al 1999, Turnbull 1999, Chile (Kibenge et al 2001), Faroes (Anonymous 2000) and the USA (Bouchard et al 2001). Typical pathological changes are severe anaemia, leucopenia, ascites and haemorrhagic liver necrosis (Thorud & Djupvik 1988, Evensen et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…El primer brote de virus ISA se registró en Noruega en 1984 (Thorud & Djupvik, 1988) y desde entonces la enfermedad se ha registrado en todos los principales países productores de salmón del Atlántico: Canadá (Mullins et al, 1998;Ritchie et al, 2001), Escocia (Rodger et al, 1998;Rowley et al, 1999), Estados Unidos (Maine) (Bouchard et al, 2001), Islas Faroe (Lyngøy, 2003) y Chile (Kibenge et al, 2001;Godoy et al, 2008). La especie más susceptible es el salmón del Atlántico (S. salar), pero también logra sobrevivir e infectar a la trucha de mar (Salmo trutta), trucha arcoiris (Onchorhynchus mykiss) y salmon coho (O. kisutch) (Kibenge et al, 2001), los cuales no manifiestan la enfermedad pero pueden actuar como vectores y reservorios del virus ISA (Nylund et al, 1995Hastein, 1997;Rolland & Nylund, 1998).…”
unclassified
“…La especie más susceptible es el salmón del Atlántico (S. salar), pero también logra sobrevivir e infectar a la trucha de mar (Salmo trutta), trucha arcoiris (Onchorhynchus mykiss) y salmon coho (O. kisutch) (Kibenge et al, 2001), los cuales no manifiestan la enfermedad pero pueden actuar como vectores y reservorios del virus ISA (Nylund et al, 1995Hastein, 1997;Rolland & Nylund, 1998).…”
unclassified
“…Although, ISA virus (ISAV) outbreaks were observed only in Atlantic salmon, the virus was detected from apparently healthy animals in other species (Raynard et al, 2001). The only exception was the isolation of ISAV from diseased Coho salmon (Oncorhynchus kisutch) in Chile in 1999 (Kibenge et al, 2001). Experimental infections showed that other species could be susceptible to ISAV infection, especially juvenile rainbow trout (Oncorhynchus mykiss) for which mortality was recorded after both virus injection and bath immersion, which may represent a threat to the trout industry (Biacchesi et al, 2007).…”
mentioning
confidence: 99%